Custos de transação e capacitações: influência nas estruturas de governança no setor farmacêutico do Brasil - Nogueira, Antonio Carlos Lima (2012)
The study aimed to analyze the influence of transaction costs and capabilities on vertical integration for the manufacturing step in the pharmaceutical sector in Brazil. This objective resulted from the potential contribution to the ongoing research agenda on the relationship between the approaches of transaction costs and capabilities. The universe of research is the total number of drugs registered at the National Agency of Sanitary Surveillance (ANVISA), which is the federal regulator or drugs in Brazil. The population is the subset of drugs available in the public database Bulário Eletrônico and the levels of analysis are the constructs of vertical integration, experience, diversification, asset specificity and bargaining power. The unit of analysis is the transaction of drug manufacturing and the object of analysis is the registry of the drug. I developed and proposed a structural model composed of a set of hypotheses with causal relationships between constructs. The model includes first order latent variables and measurable indicators based on data available on database and in the websites of the companies. With these definitions, I collected the data for each drug, including pharmaceutical form, therapeutic class, regulatory category and vertical integration of the manufacturing transaction. To test the hypotheses I conducted a confirmatory factor analysis of the measurement model through a structural equation model solved by Partial Least Squares. The first theoretical implication of the results is the identification of significant relationships between constructs related to transaction costs (asset specificity and bargaining power) and capabilities (experience and diversification) as well as relations between vertical integration and the other constructs. The second implication is the positive relationship between diversification and vertical integration. As diversification is an indicator of capabilities, the result implies that the limits of the firm reflect a bundle of capabilities expressed by processes and routines. The result could be subject to criticism that the vertical integration adoption may be resultant of cost considerations and delimitation of the scope based on the stages of greatest value to the company. The third implication is the existence of a negative relationship between asset specificity and vertical integration. The result seems to indicate the low strategic value of the manufacturing transaction in the value chain in the pharmaceutical industry. It seems that companies tend to outsource manufacturing transaction precisely for products with specific attributes. The fourth implication is the lack of influence of bargaining power on vertical integration. This result may be due to two aspects: the first is the very structure of the market portrayed by population and second is the low importance of transaction registration to generate value. In this population, the market is competitive for the more widespread forms and classes and more concentrated for products with rarer forms and classes. On the other hand, the low relevance of the transaction as a strategic activity can make decisions on vertical integration does not take into account the bargaining power of the company.